Student athlete well-being framework: an empirical examination of elite college student athletes - Sato, Shintaro; Kinoshita, Keita; Kondo, Midori; Yabunaka, Yuki; Yamada, Yaeko; Tsuchiya, Hironobu (Frontiers in Psychology, 2023)
The current study proposes a multidimensional student athlete well-being framework (SAWBF). The authors used 12 items to capture SAWBF comprised of four well-being dimensions (i.e., physical, hedonic, psychological, and social well-being). To empirically assess the reliability and validity of the framework, data from elite collegiate student athletes in Japan (N = 546) were procured. The results indicated sufficient convergent and discriminant validities of SAWBF. The authors also assessed predictive validity correlations of the framework by focusing on the oft-supported well-being outcome – organizational citizenship behavior, which were also found to be associated with SAWBF. The findings indicated the usefulness of SAWBF; and coaches and staff members can utilize the framework to multi-dimensionally understand well-being status of their student athletes, potentially boosting adaptive behaviors.